2012
DOI: 10.4028/www.scientific.net/amr.510.799
|View full text |Cite
|
Sign up to set email alerts
|

Cation Exchange Detection in the Process of Ionic Soil Stabilizer Reinforcing Soil by Laser-Induced Breakdown Spectroscopy <sup></sup>

Abstract: In order to study the process of ionic soil stabilizer (ISS) reinforcing different kinds of soil, kaolin, red clay, landslide soil, expansive soil and quartz sand ,the five kinds of standard soil samples were treated by ISS of ratio 1:100. After 24-hour soaking and oscillation treatment, the supernatant was detected by laser-induced breakdown spectroscopy (LIBS). Comparing with the samples had not been treated by ISS, got the information of cation exchange. Experimental results showed that, the cation exchange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The experimental system used in this study for LIBS analysis has been previously described in our work. [41][42][43] It includes a neodymium-doped yttrium aluminum garnet (Nd:YAG) laser and a medium-order grating spectrometer with an intensified charge-coupled device (ICCD) camera. When the highenergy pulsed laser emitted from the Nd:YAG (Pro-290 from Spectra-Physics) was focused on the sample's surface, the LIBS was collected through a light-receiving system (ME-OPT-007 receiver from Andor), a spectrometer (ME 5000 from Andor), and an ICCD camera (DH734-18U-03 from iStar/Andor) in sequence, and transformed into spectral signals.…”
Section: Experimental Systemsmentioning
confidence: 99%
“…The experimental system used in this study for LIBS analysis has been previously described in our work. [41][42][43] It includes a neodymium-doped yttrium aluminum garnet (Nd:YAG) laser and a medium-order grating spectrometer with an intensified charge-coupled device (ICCD) camera. When the highenergy pulsed laser emitted from the Nd:YAG (Pro-290 from Spectra-Physics) was focused on the sample's surface, the LIBS was collected through a light-receiving system (ME-OPT-007 receiver from Andor), a spectrometer (ME 5000 from Andor), and an ICCD camera (DH734-18U-03 from iStar/Andor) in sequence, and transformed into spectral signals.…”
Section: Experimental Systemsmentioning
confidence: 99%
“…Furthermore, the simple structure of LIBS systems allows for design of portable devices for field use (Knadel et al, 2017;Yamamoto, Cremers, Ferris, & Foster, 1996). Previous studies have reported the application of LIBS for quantitative analysis of soil properties, including soil texture (Villas-Boas et al, 2016), pH (Ferreira, Neto, Milori, Ferreira, & Anzano, 2015), CEC (Liu, Zeng, Zhang, Liu, & Lin, 2012), C (Cremers et al, 2001;Martin et al, 2010;Nguyen, Moon, & Choi, 2015), and N, P, and K (Dong, Zhao, Zheng, Zhao, & Jiao, 2013;Lu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%